Green economy metrics as a promoter of sustainable development in universities. Case study: El Bosque University - Romero-Infante, Jaime Alberto; Ramírez, Mónica Sofía Rico; Luna, Luz A.; Leguizamon, Sergio; Verjel, Elissa (Journal of Sustainability Perspectives, 2022)
The exchange that occurs in universities when they participate in international rankings is an important space to share and grow in the academic production of teachers and in the training of students. At the beginning, the sustainable social responsibility system was adhered only to the industry due to the increase in large-scale production; however, the academy has taken a voice and vote on this climate phenomenon. This is why projects aimed at sustainability have been proposed in universities that aim at a green economy. Likewise, the UI Green Metric Rankings allows higher education institutions worldwide to measure their sustainable actions in different categories on a voluntary basis.For this reason, this article presents the best practices of the University El Bosque against the different indicators that the UI Green Metric measures, such as infrastructure, energy and climate change, waste, water, transport and education. Consequently, the concept of sustainability has become a vital element for the development of programs that involve the institution in internationalization through the global recognition generated by being participants and being able to be in the range of green universities.As a conclusion of this exchange, Based on responsible production methods with the natural and social environment or Clean Modalities, a production cycle is proposed that opens the possibility of integrating with other related production systems that receive their waste as raw materials in a network, this is Symbiotic Cycle. To arrive at the approach of a symbiotic disposal of waste as inputs with other production systems in such a way as to consolidate a set of sustainable organizations that collaborate with each other and that continuously recover the value to increase efficiency.Keyword: sustainability, green economy, sustainable development